Conditioned Medium of Induced Mesenchymal Stem Cells as an Activator of Differentiation in The Osteogenic Direction: Life Sciences-Medicine - S.V, Nadezhdin; V.S, Belyaeva; N.A, Nadezhdina; L.A, Pokrovskaya; V.I, Shutov; S.V, Volobueva; D.V, Maklakov; M.V, Pokrovskii (International Journal of Life Science and Pharma Research, 2022)
In the prevailing era, the need for new biologically active substances of peptide nature and their therapeutic impacts are of great interest of the contemporary pharmacology. Hence, this study intends to assess the osteoinductive potential of the conditioned medium concentrate on native mesenchymal stem cells. To gratify the study’s aim, this study was carried out on a culture of rat mesenchymal stem cells. To stimulate the differentiation of Mesenchymal stem cells in the osteogenic direction, this study used a complete nutrient medium containing dexamethasone, ascorbic acid, sodium ß -glycerophosphate in the concentrations recommended in the guidelines. Subsequently, the resulting concentrate sample was examined using HPLC-MS / MS mass, spectrometric analysis. Part of the previously obtained concentrate of the conditioned medium was used, to assess the proliferation and differentiation of rat Mesenchymal stem cells in the osteogenic direction by staining for alkaline phosphatase. Given the results of the study, it can be concluded that that most of the identified proteins of the conditioned medium concentrate belong to the group of proteins regulating cellular processes, and groups of proteins were also, found that relate to the organization of the extracellular structure, the processes of cell development, or are directly responsible for the differentiation of Mesenchymal stem cells in the osteogenic direction. Along with this, the concentrate of the conditioned medium does not affect the proliferation rate of Mesenchymal stem cells. Thus, the resulting concentrate of the conditioned medium, can be further used, for the development of therapeutic preparations with osteoinductive and regenerative potential.